The Relationship Between Parental Patterns and The Incidence of Teenage Pregnancy - Anik Sri Purwanti; Nirwati Nirwati (Journal of Educational Innovation and Public Health, 2025)
Background: Teenage pregnancy remains a significant public health concern due to its potential risks to both mother and child, including health complications, social challenges, and educational disruption. One of the factors influencing teenage pregnancy is parental patterns, which include parenting styles, communication, supervision, and emotional support. Studies have shown that adolescents from families with authoritarian or neglectful parenting are more likely to engage in risky sexual behavior, increasing the risk of early pregnancy. Understanding the relationship between parental patterns and teenage pregnancy can help develop targeted interventions to prevent adolescent pregnancies. Objective: This study aimed to examine the relationship between parental patterns and the incidence of teenage pregnancy. Methods: A quantitative analytical study with a cross-sectional design was conducted. The sample consisted of 30 teenage mothers selected using a total sampling technique. Data were collected through structured questionnaires assessing parental patterns, including communication, supervision, and emotional support, as well as information about pregnancy incidence. Data analysis was performed using the Wilcoxon signed-rank test to determine the statistical relationship between parental patterns and teenage pregnancy incidence. Results: The study found that 30 respondents (100%) reported experiencing parental patterns that influenced their behavior. Among them, teenagers from families with supportive and communicative parenting had a lower risk of teenage pregnancy. The Wilcoxon signed-rank test showed a significant relationship between parental patterns and the incidence of teenage pregnancy (p = 0.000), indicating that parental guidance and involvement play a critical role in preventing early pregnancy. Conclusion: There is a significant relationship between parental patterns and the incidence of teenage pregnancy. Supportive and communicative parental patterns reduce the likelihood of teenage pregnancy, while neglectful or authoritarian patterns increase the risk. These findings highlight the importance of parental involvement, education, and guidance in adolescent reproductive health.